Etika Bisnis Pedagang pada Jual Beli Telepon Genggam Bekas Ditinjau dari Perspektif Ekonomi Islam di Kecamatan Selong Kabupaten Lombok Timur - Lalu Muh Shabiran; Titiek Herwanti; Ihsan Rois (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
The purpose of this research is to know about business ethics of used mobile phone traders in Kecamatan Selong, East Lombok regency. The reason is studied, because East Lombok especially in Kecamatan Selong is area which majority of Moslem, and its people many who trades as trader especially in buying and selling of used mobile phone. besides East Lombok is an area that has many master teachers and kyai who understand the science of religion. Based on the above reasons, the researcher assumes that the merchant will run the buying and selling in accordance with the ethics of Islamic business but in fact many traders who only prioritize profit by memamfaatkan buyer ignorance. This research is conducted by qualitative approach, which process using triangulation technique as data collection and analyze the result. Focus of this research is to know the ethics of merchant business on buying and selling of used mobile phones in Selong Sub-district, East Lombok. The results of research on how the business ethics of used mobile phone dealers in Selong Sub-district are open traders on used mobile phone conditions, in taking advantage of high traders exploiting buyer ignorance, in obtaining the old geggam phone from the merchant community lowering the price and sell at the highest price.